Application of Western Blotting for the Post-Treatment Monitoring of Human Cystic Echinococcosis. - Rajesh Kumar Tenguria; Mohd Irfan Naik; Bashir Fomda (Tehran University of Medical Sciences, 2013)
Cystic echinococcosis (CE) is one of the most important parasitic zoonosis worldwide. Due to the high recurrence rate of the disease after surgery, follow up of the patient is necessary. The aim of current research was to assess the performance of Western blotting (WB), using sheep hydatid fluid, for serological diagnosis and post-treatment monitoring of human CE.Serum samples obtained from 50 clinically/radiologically proven cases of CE along with serum samples from non-CE patients and healthy persons were tested by WB, using sheep hydatid fluid as antigen.The WB test enabled the detection of antibodies in the pre-operative samples for proteins of 18-239 kDa in molecular weight. From 50 sera of CE patients, 31 cases (72.09%) detected 52 kDa subunit, 27 cases (62.79%) detected 24 kDa band, 26 cases (60.46%) recognised 39 kDa band and 21 cases (48.83%) identified 46 kDa component of sheep hydatid antigen. Sera from patients with other parasitic infections and malignancy showed cross-reactivity with the cluster of 54-59 kDa bands. The healthy control sera were not reactive to any antigenic fraction. The antigenic bands with molecular weight of 52, 24, 39 and 46 kDa were specific for CE, and may serve as useful diagnostic markers. The antibodies specific to proteins 24 and 39 kDa significantly decreased in the patients cured after surgery, while in patients with recurrent parasitism the bands present before surgery persisted.The WB with sheep hydatid antigen might be useful in the diagnosis and post-surgical monitoring of CE patients.